2007
DOI: 10.1007/s00464-007-9566-4
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic responses of human peritoneal fluid in laparoscopic cholecystectomy: a prospective clinical study

Abstract: Fibrinolytic changes in peritoneal fluid have several similarities in open and laparoscopic cholecystectomies with regard to tPA activity and PAI-1 levels. However, higher tPA levels after the open procedure probably are secondary to more intense tissue handling leading to mesothelial release of tPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In the light of our own results and contrary to common opinion, it can be concluded that peritonitis does not inhibit intraperitoneal fibrinolytic activity. The existence of intraperitoneal fibrinolysis has been confirmed in observations by Tarhan et al, however, the authors showed the presence of another plasminogen activator, t-PA [11]. Similarly to our analysis of peritoneal fluid, Brokelman et al also showed the presence of uPA, concluding that there is no place for a further hypothesis of inhibition of intraperitoneal fibrinolysis during peritonitis [18].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the light of our own results and contrary to common opinion, it can be concluded that peritonitis does not inhibit intraperitoneal fibrinolytic activity. The existence of intraperitoneal fibrinolysis has been confirmed in observations by Tarhan et al, however, the authors showed the presence of another plasminogen activator, t-PA [11]. Similarly to our analysis of peritoneal fluid, Brokelman et al also showed the presence of uPA, concluding that there is no place for a further hypothesis of inhibition of intraperitoneal fibrinolysis during peritonitis [18].…”
Section: Discussionsupporting
confidence: 85%
“…A reduced peritoneal fibrinolytic capacity after surgery is pointed out by many authors. Many of them regard it as the main cause of postoperative adhesions [11,12,13]. It is confirmed by other studies which have shown that peritoneal fibrinolytic activity could be depressed not only by surgery but also by inflammatory process of the peritoneum [14].…”
Section: Introductionmentioning
confidence: 73%
“…Tarhan et al have recently decribed the fibrinolytic changes in peritoneal fluid after a cholecystecomy and observed similarities in conventional and laparoscopic cholecystectomies with regard to tPA activity and PAI-1 levels. 17 The timing of the biopsies is an issue that should be addressed. In the present study, we chose to take biopsies at specific moments during the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Tarhan et al [70] studied peritoneal fluid after both open and laparoscopic cholecystectomy. They found higher tPA levels after the open procedure, possibly in relation to more intense tissue handling.…”
Section: Methodsmentioning
confidence: 99%